1998
DOI: 10.1007/s004210050415
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic activity is not dependent upon exercise mode in post-myocardial infarction patients

Abstract: In this study we investigated possible differences in fibrinolytic activity in cardiac patients while they performed treadmill and cycle ergometry. Thirteen post-myocardial infarction patients completed two maximal exercise tests on treadmill and cycle ergometers. Blood was collected before and after each exercise test and was analyzed for the fibrinolytic variables, tissue plasminogen activator (t-PA) and plasminogen activator inhibitor-1 (PAI-1) activity, and lactate. Maximal oxygen uptake, heart rate, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
(52 reference statements)
0
3
0
1
Order By: Relevance
“…Furthermore, PAI-1 levels tend to be elevated even in healthy sedentary individuals [ 43 ]. A strong body of evidence has demonstrated the acute anti-fibrotic response following exercise [ 44 , 45 , 46 , 47 , 48 , 49 ]. Not only does exercise normalize PAI-1 levels in healthy subjects, but also in diseased populations [ 50 , 51 , 52 , 53 ].…”
Section: Therapeutic Interventions To Normalize Pai-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PAI-1 levels tend to be elevated even in healthy sedentary individuals [ 43 ]. A strong body of evidence has demonstrated the acute anti-fibrotic response following exercise [ 44 , 45 , 46 , 47 , 48 , 49 ]. Not only does exercise normalize PAI-1 levels in healthy subjects, but also in diseased populations [ 50 , 51 , 52 , 53 ].…”
Section: Therapeutic Interventions To Normalize Pai-1mentioning
confidence: 99%
“…Indeed, several studies have identified the importance of plasminogen system function but have yet to fully elucidate a role for PAI-1 in skeletal muscle [ 35 , 36 , 37 , 38 , 39 , 40 ], although recent evidence suggests that skeletal muscle is also a site of PAI-1 synthesis [ 29 , 41 , 42 ]. Control of PAI-1 levels in the circulation is of clinical importance and while studies generally indicate that circulating PAI-1 can be controlled with exercise [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] or through the administration of pharmacological PAI-1 inhibitors [ 17 , 22 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. This review will summarize the biology of PAI-1 and the plasminogen system as it relates to overall tissue function and ECM remodeling, highlight the role of PAI-1 in skeletal muscle, and shed light on potential therapeutic strategies to reduce or normalize PAI-1 levels in an attempt to improve muscle and overall health.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported an increased fibrinolytic response following strenuous exercise in patients with CAD with decreased PAI-1 [35][36][37][38][39][40] and increased t-PA [35][36][37][38][39]41,42]. Three studies included a group with healthy controls, and all results were similar to the CAD group [37,38,40].…”
Section: Discussionmentioning
confidence: 80%
“…Οι Fernhall και συν. 148 υπέβαλαν σε οξεία μέγιστη ισοτονική ή/και ισομετρική σωματική κόπωση άτομα που είχαν υποστεί καρδιαγγειακό επεισόδιο. Οι ερευνητές αυτοί διαπίστωσαν ότι, αμέσως μετά το πέρας της προσπάθειας η δραστηριότητα του t-PA στο αίμα αυξήθηκε και εκείνη του PAI-1 παρουσίασε τάσεις μείωσης.…”
Section: οξεία σωματική κόπωση και επίπεδα T-pa και Pai-1unclassified